Integration of Blockchain Technology in the Criminal Justice System: Challenges of Regulation, Data Security, and Legitimacy of Digital Evidence - Robby Malaheksa; Heni Siswanto; Agus Triono (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
The development of digital technology has brought significant changes to the criminal justice system, particularly in the management of digital evidence. However, challenges such as data manipulation, evidence validity, and storage security remain significant issues. Blockchain, a technology that offers transparency, security, and data traceability, has great potential for application in the criminal justice system for more effective digital evidence management. This study aims to analyze the application of blockchain in the criminal justice system, particularly in relation to the validity of evidence, integrity, and digital evidence management. The methods used include a literature review and comparative analysis of conventional systems and blockchain-based models. The findings show that the implementation of blockchain can improve the security and protection of digital evidence through hashing and encryption mechanisms that are difficult to manipulate. In addition, this technology enables the decentralized recording of digital evidence transactions, thereby reducing the risk of abuse by certain parties. Therefore, the adoption of blockchain technology in the criminal justice system has the potential to strengthen the credibility and efficiency of the legal evidence process. [Perkembangan teknologi digital telah membawa perubahan signifikan pada sistem peradilan pidana, terutama dalam pengelolaan bukti digital. Namun, tantangan seperti manipulasi data, validitas bukti, dan keamanan penyimpanan tetap menjadi masalah utama. Blockchain, sebagai teknologi yang menawarkan transparansi, keamanan, dan jejak data, memiliki potensi besar untuk diterapkan dalam sistem peradilan pidana guna pengelolaan bukti digital yang lebih efektif. Artikel ini bertujuan untuk menganalisis penerapan blockchain dalam sistem peradilan pidana, khususnya terkait validitas bukti, integritas, dan pengelolaan bukti digital. Metode yang digunakan meliputi tinjauan literatur dan analisis perbandingan antara sistem konvensional dan model berbasis blockchain. Temuan menunjukkan bahwa implementasi blockchain dapat meningkatkan keamanan dan perlindungan bukti digital melalui mekanisme hashing dan enkripsi yang sulit dimanipulasi. Selain itu, teknologi ini memungkinkan pencatatan terdesentralisasi transaksi bukti digital, sehingga mengurangi risiko penyalahgunaan oleh pihak tertentu. Oleh karena itu, adopsi blockchain dalam sistem peradilan pidana berpotensi memperkuat kredibilitas dan efisiensi dalam proses bukti hukum].